Volunteering to Support Refugees: A Question of One’s Scope of Justice - Kals, Elisabeth; Strubel, Isabel Theresia (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2017)
Who volunteers on behalf of refugees, on the basis of what motives? Questionnaire data (N = 271) reveal that people who volunteer, and those who do not, share differentiated perceptions of fairness about refugee aid. However, volunteers have a broader and more inclusive scope of justice than a matched group of non-volunteers. The scope of justice proves to be a powerful construct when explaining the willingness to volunteer beyond group membership (volunteers vs. non-volunteers) and the functional approach. Perceptions of fairness, especially the scope of justice, should therefore be considered in order to understand differences in reactions towards refugees if moral exclusion is to be avoided.